2014
DOI: 10.1007/s00442-014-2979-6
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of bird community composition: an analysis of baseline conditions from long-term data

Abstract: Numerous anthropogenic activities threaten the biodiversity on earth. Because all ecological communities constantly experience temporal turnover due to natural processes, it is important to distinguish between change due to anthropogenic impact and the underlying natural rate of change. In this study, we used data sets on breeding bird communities that covered at least 20 consecutive years, from a variety of terrestrial ecosystems, to address two main questions: (1) How fast does the composition of bird commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…) or slow temporal changes occurring over decades (Kampichler et al . ). Grasshoppers, which include C 3 and C 4 specialists (Engel et al .…”
Section: Discussionmentioning
confidence: 99%
“…) or slow temporal changes occurring over decades (Kampichler et al . ). Grasshoppers, which include C 3 and C 4 specialists (Engel et al .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of community composition studies are of short duration (1-2 yr; Marzluff et al 2001, Kampichler et al 2014, but a growing body of longitudinal studies of urban biotic communities is emerging. A recent review found 34 studies of urban birds that encompass five or more years of sampling (Fidino and Magle 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to a RDA, the first canonical AEM axis represents the dominant pattern in the data and the second AEM axis the next most important pattern. In essence, AEM modelling facilitates the identification of different temporal scales (i.e., from seasonal, to decadal to millennial scales) in complex time series data (Baho, Futter, Johnson, & Angeler, ) and has been widely applied to different ecosystems and taxa (invertebrates: Angeler, Allen, & Johnson, ; birds: Kampichler et al, ; paleolimnology: Spanbauer et al, ; microscopy‐based phytoplankton: Angeler, Allen, & Johnson, ; insects: Blanchet et al, ), well supporting its explanatory power. The fitted site scores (i.e., linear combination of explanatory variables; lc scores) of the first and second canonical AEM axis were plotted along time to identify the temporal variability of communities at different temporal scales.…”
Section: Methodsmentioning
confidence: 99%